Prevalence of dental caries and dental fluorosis among 12 and 15 years old school children in relation to fluoride concentration in drinking water in an endemic fluoride belt of Andhra Pradesh - Chandra Shekar; Manjunath Bhadravathi Cheluvaiah; Dinesh Namile (Wolters Kluwer Medknow Publications, 2012)
Background: The published literature on the prevalence and severity of dental caries and dental fluorosis among school going children in Nalgonda district - An Endemic Fluoride belt was lacking . Objectives: To assess the prevalence and severity of dental fluorosis and dental caries among 12 and 15 years old children in relation to fluoride concentration in drinking water . Settings and Design: It was a cross-sectional study, done in Nalgonda district of Andhra Pradesh, India (endemic fluoride belt) . Materials and Methods: 5 of the 59 mandals in the district of Nalgonda were selected by simple random sampling. Then, 3 schools from each of these selected mandals were chosen at random. All the eligible 6 th and 9 th standard children were considered for final analysis. The demographic and other relevant information was collected by 3 trained and calibrated dentists, using a structured questionnaire. Dental caries were recorded using dentition status and treatment needs and fluorosis were recorded by Dean's fluorosis index. The statistical analysis was done using SPSS version 16. Results: The prevalence of dental caries among children was 56.3% with the highest in below optimal fluoride area (71.3%) and lowest in optimal fluoride area (24.3%). The prevalence of dental fluorosis was 71.5%. The prevalence was 39.7% in below optimal fluoride area and 100% in high and very fluoride areas. The prevalence and severity of fluorosis increased with increasing fluoride concentration. The caries experience was more among boys than girls. Conclusion: There was a negative correlation between dental caries and fluoride concentration for the entire study population. However, in high fluoride areas, there was a positive correlation between fluoride concentration and dental caries. Water defluoridation on an urgent basis is a priority here than water fluoridation, because the prevalence and severity of dental flurorosis is very high.